2020
DOI: 10.5852/ejt.2020.660
|View full text |Cite
|
Sign up to set email alerts
|

Three new species and new records of the genus Centromerus (Araneae, Linyphiidae) from Italy

Abstract: Three new species of the genus Centromerus from Italy, C. tongiorgii sp. nov., C. hanseni sp. nov., and C. gatoi sp. nov., are described for the first time on the basis of both male and female specimens. Their relationships with other congeneric species, as well as their diagnoses, are discussed using morphological characters. New records of poorly known species of Centromerus from Italy are furthermore reported. Among them, C. desmeti Bosmans, 1986 is reported for the first time for the Italian fauna and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 885 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This species, described from France ( Mazzia and Cornic 2020 ) and recently found in Italy for the first time ( Trotta 2024 ), was collected in agricultural patches that are common in the Appia Antica Regional Park. On the whole, six Italian endemic species were found in the study area: Dysdera romana , known exclusively from lowland and hillside localities near the Tyrrhenian coast of central and south Latium and from Emilia-Romagna ( Gasparo and Di Franco 2008 , Lami et al 2023 ); the recently-described Centromerus tongiorgii , which was already found in Latium at Canale Monterano ( Ballarin and Pantini 2020 ), but which is also present in Abruzzo, Basilicata, Marche, Umbria, Emilia-Romagna, Liguria, Lombardy and Veneto ( Ballarin and Pantini 2020 , Nardi and Marini 2021 ); Cybaeodes marinae a nocturnal spider found in Thyrrenian areas of Latium, Sardinia, Calabria, Sicily, Liguria and Tuscany ( Di Franco 1989 , Pantini and Mazzoleni 2018 , Picchi 2020 , Caria et al 2021 , Trotta 2023 ); Harpactea sardoa found in south Sardinia and Latium ( Alicata 1966 , Brignoli 1979a ); Pseudeuophrys perdifumo , only known from a few sites in Calabria and Campania ( Van Helsdingen 2015 ); Nemesia bosmansi , recently described by Decae (2024) from sandy dunes of the Parco Nationale del Circeo (Latium). It is also important to mention some species with limited distribution like Araeoncus longisculus and Syedra nigrotibialis , which can be found only in mainland Italy, Sardinia and Corsica ( Simon 1926 , Müller 1986 , Pantini and Isaia 2019 ); Dysdera lantosquensis , which has an Alpino-Appenninic distribution and is mainly distributed in central and northern Italy and on the French border ( Řezáč et al 2018 ); Dysdera bottaziae , an Appennino-Dinaric sub-endemic species found in southern Italy, Croatia and Bosnia and Herzegovina (…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species, described from France ( Mazzia and Cornic 2020 ) and recently found in Italy for the first time ( Trotta 2024 ), was collected in agricultural patches that are common in the Appia Antica Regional Park. On the whole, six Italian endemic species were found in the study area: Dysdera romana , known exclusively from lowland and hillside localities near the Tyrrhenian coast of central and south Latium and from Emilia-Romagna ( Gasparo and Di Franco 2008 , Lami et al 2023 ); the recently-described Centromerus tongiorgii , which was already found in Latium at Canale Monterano ( Ballarin and Pantini 2020 ), but which is also present in Abruzzo, Basilicata, Marche, Umbria, Emilia-Romagna, Liguria, Lombardy and Veneto ( Ballarin and Pantini 2020 , Nardi and Marini 2021 ); Cybaeodes marinae a nocturnal spider found in Thyrrenian areas of Latium, Sardinia, Calabria, Sicily, Liguria and Tuscany ( Di Franco 1989 , Pantini and Mazzoleni 2018 , Picchi 2020 , Caria et al 2021 , Trotta 2023 ); Harpactea sardoa found in south Sardinia and Latium ( Alicata 1966 , Brignoli 1979a ); Pseudeuophrys perdifumo , only known from a few sites in Calabria and Campania ( Van Helsdingen 2015 ); Nemesia bosmansi , recently described by Decae (2024) from sandy dunes of the Parco Nationale del Circeo (Latium). It is also important to mention some species with limited distribution like Araeoncus longisculus and Syedra nigrotibialis , which can be found only in mainland Italy, Sardinia and Corsica ( Simon 1926 , Müller 1986 , Pantini and Isaia 2019 ); Dysdera lantosquensis , which has an Alpino-Appenninic distribution and is mainly distributed in central and northern Italy and on the French border ( Řezáč et al 2018 ); Dysdera bottaziae , an Appennino-Dinaric sub-endemic species found in southern Italy, Croatia and Bosnia and Herzegovina (…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on the araneofauna of Rome date back to the late 19 th and early 20 th century ( Lucas 1869 , Pavesi and Pirotta 1878 , Antonelli 1911 ). Subsequently, studies in the area were carried out by Brignoli ( Brignoli 1966 , Brignoli 1967b , Brignoli 1971 , Brignoli 1972 , Brignoli 1977 , Brignoli 1979a , Brignoli 1979b ), Di Franco ( Di Franco 1989 , Di Franco 1992 , Di Franco 1996 , Di Franco 1997 ) and other specialists, but most of these studies consist of point records or studies that refer to a few spider families ( Millidge 1977 , Gasparo 1996 , Gasparo and Di Franco 2008 , Pantini and Isaia 2008 , Lacasella et al 2014 , Ballarin and Pantini 2020 ). To contribute to fill this gap, we present here the results of a study aimed at assessing the species diversity of the ground spiders of a large protected green space in urban Rome, the Appia Antica Regional Park.…”
Section: Introductionmentioning
confidence: 99%